SHARIA BANK FINANCING IN IMPROVING THE WELFARE OF MSMEs: BASED ON MAQASHID SHARIA - Indrarini, Rachma (Universitas Airlangga, 2017)
The growing workforce population in Indonesia has led to an increase in job seekers. However, the ratio between the workforce and available jobs shows that the workforce is larger, resulting in unemployment. When an individual is unemployed, they cannot fully meet their needs, which leads to a decline in welfare. One way to tackle the problem of unemployment is to encourage people to become entrepreneurs and provide financing to MSMEs (Micro, Small and Medium Enterprises). It is hoped that with financing, MSMEs can improve their welfare. This research is a descriptive qualitative study that examines BPRS Financing in Improving the Welfare of MSMEs with the welfare indicator being maqashid sharia (Religion, Soul, Mind, Progeny, and Wealth). The results of this study show an increase in the welfare of MSME customers after receiving financing from BPRS. Keywords: Financing, MSMEs, Sharia objectives